Biological Assessment of Trophic Status in Riam Kanan Reservoir, Indonesia - Aswin Nur Saputra; Muhammad Muhaimin; Herlina Herlina (JPG (Jurnal Pendidikan Geografi), 2026)
Understanding nutrient–biomass relationships is essential for assessing trophic dynamics in tropical reservoirs experiencing increasing anthropogenic pressure. This study evaluates the biological condition and trophic status of Riam Kanan Reservoir, South Kalimantan, Indonesia, using field measurements of chlorophyll-a, dissolved phosphate, and water transparency across 20 sampling stations. Sampling locations were spatially delineated using Landsat 8 composite imagery to ensure representative coverage of major hydrological zones. Statistical analyses included descriptive statistics, regression modeling, and Carlson’s Trophic State Index (TSI). Chlorophyll-a concentrations ranged from 2.48 to 7.18 µg L⁻¹ (mean 3.94 ± 1.26 µg L⁻¹), while dissolved phosphate exhibited high spatial variability (1–385 µg L⁻¹; mean 86.20 ± 99.18 µg L⁻¹). Secchi depth varied between 1.60 and 2.56 m (mean 2.18 ± 0.26 m). Regression analysis revealed a significant positive relationship between dissolved phosphate and chlorophyll-a (R² = 0.278, p < 0.05), indicating that phosphorus availability contributes to phytoplankton biomass variability. However, chlorophyll-a did not significantly explain transparency variation, suggesting that non-algal turbidity influenced optical conditions. TSI values derived from chlorophyll-a and Secchi depth consistently classified the reservoir as mesotrophic. The results indicate moderate biological productivity with localized nutrient enrichment and partial nutrient–biomass coupling. Spatial heterogeneity in phosphate suggests potential external inputs and internal loading processes. Integrated nutrient management and sustained multi-parameter monitoring are recommended to prevent trophic escalation under increasing anthropogenic and climatic pressures.